Estimação da população de motores elétricos industriais no brasil para potências integrais acima de 1 cv - Mendonça, Felipe Augusto da Silva (Universidade Federal Rural do Semi-Árido, 2020)
Taking into account the great ignorance of government agencies about the population of motors in Brazil, as well as their energy performance, there is a need to estimate the population of motors in the country. The present work aims to estimate the population of industrial electric motors in Brazil for powers above 1 hp, where a national history of sales of electric motors was built, using data from the Associação Brasileira da Indústria Elétrica e Eletrônica (ABINEE) and a demand forecasting method to obtain sales data for the year 2019. From the sales data and annual motor data at the end of their useful life, the net balance of electric motors was determined. Through the calculation the net balance of motors population and comparisons made, it was found that the values for the population in 2005 were approximately 9.2 million units, in 2012 or more approximately 16.3 million units, one year later, the value was 17.7 million units and, in 2018, it was 22.6 million motors, a value that approximates the value cited by Souza et al (2019).
Keywords: Motores elétricos; eficiência energética; previsão de vendas; saldo líquido de motores; ENGENHARIAS::ENGENHARIA ELETRICA